Pretrial detention and the decision to impose bail in Southern California - Ottone, Sarah (Criminology, criminal justice, law & society, 2018)
This paper examines pretrial judicial decision making, specifically the decision to impose bail. At the bail hearing,judges must decide whether defendants should be detained, released on their own recognizance, or granted bail. In California, judges make this decision largely by relying on County Bail Schedules, which are similar to sentencing guidelines and prioritize the seriousness of the charged offense when determining bail. Being detained pretrial, either due to the denial of bail or the inability to afford the bail that was set has negative implications, including the fact that defendants who are denied bail are more likely to plead guilty, and upon conviction are more likely to be sentenced to incarceration. They also face longer sentences than defendants who are released pending trial. Despite the significant impact of the bail decision, there is limited research on the decision, including on the factors judges consider in making the bail decision and how judges make the decision. This paper presents the results of a qualitative study of bail hearings in two California counties. Relying on court observations and interviews, it finds that bail schedules are the most important factor considered by judges and that bail is usually set without regard to the ability of the defendant to pay.